The historical based learning model for improving students’ learning outcome - Fitroh, Ismaul (Journal of Research in Instructional, 2024)
There are many university students who get a disappointing learning outcome in the course of Indonesia history in hindu-buddha period, indicated by achievement score below the minimum mastery criteria that sets at score of 75. The aim of this research is analyzing the historical based learning model to students’ learning outcome in the course of Indonesia history in hindu-buddha period. This research is an experimental research with a pre-experimental research  through a one-group pretest-posttest design. Population in this research was all 65 students of Class 2022/2023 in History Education Program at the Faculty of Social Sciences, Gorontalo State University. 22 students were selected as the sample used in this research. Descriptive statistical analysis and inferential statistics used in the analysis technique, namely the t-test. The results of the t-test calculation obtained a tcount is 19.2 and ttable is 1.72, so, tcount>ttable. The lowest score in the pretest results was 40 and the highest score was 79. There were 19 students who were not complete the test while there were 3 students who were complete the test. In the posttest, the lowest score was 76 and the highest score was 94. In this posttest, all students were complete because they understood the material well. The conclusion is that the historical based learning model is effective in improving students’ learning outcome.